Validity of Inflammatory Bowel Disease Diagnoses in the Danish National Patient Registry: A Population-Based Study from the North Denmark Region - Albaek Jacobsen H; Jess T; Larsen L (Clinical Epidemiology, 2022)
Henrik Albaek Jacobsen,1,2 Tine Jess,1,2 Lone Larsen1,2 1Department of Gastroenterology and Hepatology, Aalborg University Hospital, Aalborg, Denmark; 2Center for Molecular Prediction of Inflammatory Bowel Disease, PREDICT, Department of Clinical Medicine, Aalborg University, Copenhagen, DenmarkCorrespondence: Henrik Albaek Jacobsen, National Center of Excellence PREDICT, Department of Gastroenterology and Hepatology, Aalborg University Hospital, Mølleparkvej 4, Aalborg, 9000, Tel +45 97656267, Email henrik.jacobsen@rn.dkPurpose: The Danish National Patient Registry (DNPR) is recognized for providing high-quality data. However, only a few minor studies have validated inflammatory bowel disease (IBD) diagnoses in the DNPR, reporting various degrees of validity. To pave the way for large-scale studies of IBD in Denmark, we aimed to investigate the validity of IBD among > 8000 patients registered in the DNPR between 2002 and 2020 in the North Denmark Region.Patients and Methods: To evaluate the reliability of the diagnoses in the DNPR, we initially compared all patients registered with one IBD diagnosis during 2002– 2020 to a list of already verified patients in the regional IBD database GASTROBIO. Medical records on all DNPR registered patients not on the list were manually reviewed by a gastroenterologist to verify or dismiss the IBD diagnosis. Positive predictive values (PPV) were calculated.Results: Of 8040 patients with at least one IBD diagnosis in DNPR, 5263 were already confirmed cases, leaving 2777 for medical record evaluation, of whom 849 had IBD. In total, 6112 were correctly registered with IBD based on one diagnosis, and 1343 were incorrectly registered, resulting in a PPV of 0.82 (95% CI, 0.81– 0.83). For patients registered with at least two diagnoses, the PPV was 0.95 (95% CI, 0.95– 0.96), and with at least three diagnoses, the PPV was 0.98 (95% CI, 0.98– 0.99). Results were similar for UC and CD separately. Of note, the completeness of valid cases went from 6112 to 4606 (75%; 95% CI, 74%-76%) when demanding at least two registered diagnoses and to 3320 (54%; 95% CI, 53%-56%) when demanding at least three registered diagnoses.Conclusion: Reassuringly, the validity of IBD diagnoses in DNPR is high, especially for patients registered more than once. However, the reduced completeness when applying a true case definition of at least two registered diagnoses should be considered.Keywords: inflammatory bowel disease, Danish National Patient Registry, validation, diagnosis codes, positive predictive value, completeness